A contested legitimacy. Memories of the loteo popular and transformations in the citizenship bond in the land occupations of the Metropolitan Area of Buenos Aires (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In this article, we review –from the results of a field work in the periphery of Greater Buenos Aires- some theoretical problems for the study of land occupations from a perspective focused on: a) their relationship with the notion of law and institutional distance; b) mutations in the link of citizenship of the popular sectors with the State and the status of brokerage relations; and c) territorial identities and sociabilities in contexts of socio-spatial segregation.We will argue that the changes that land occupations underwent between 1980 and 2000 must be understood in light of the mu- tations in the bond between citizenship of the popular classes and the State that questioned the notion of social integration and set new patterns of access to goods, services and social rights.
Keywords: land occupations, institutional distance, social rights, identities, sociabilities